Alpine and Subalpine Wildflowers Clear Creek Colorado - Melissa Baynes ([Place of publication not identified] : publisher unidentified)
Wildflowers, Clear Creek county Colorado.
Keywords: Wild flowers; Flowers; Colorado; Clear Creek County (Colo.)